Barriers to Accessing Medical Care in Sub-Saharan Africa in Early Stages of COVID-19 Pandemic - Swindle, Rachel; Newhouse, David (World Bank, Washington, DC, 2021)
Eighty-two percent of respondents in a sample of Sub-Saharan African (SSA) countries were able to access medical care despite the COVID-19 pandemic. Of the remaining 18 percent, about one-third reported that the COVID-19 pandemic impaired their access, either due to lockdown restrictions, facility closures, or fear of contracting the virus. 'Lack of money' was by far the most frequently reported barrier to accessing care across countries, especially for food-insecure households, two-thirds of which cited 'lack of money' as the main healthcare access constraint. Continued monitoring can help shed light on who is most at risk of not being able to access healthcare during crises. This note makes use of newly harmonized data to summarize reasons why respondents in 11 SSA countries were unable to access medical care during early COVID-19 stages.